Dampak dan sosialisasi tentang pentingnya hak nafkah anak - Nisa’, Fakhrun (Maliki Interdisciplinary Journal, 2025)
Child support rights are the legal obligations of parents to meet their children’s basic needs, including education, health, and well-being, which are crucial for the child’s optimal development. In Indonesia, despite child support rights being regulated by law and Islamic law, many children still do not receive adequate financial support, particularly in cases of parental divorce. This neglect leads to serious impacts on children’s psychological, social, and economic well-being, as they may experience feelings of neglect, anxiety, and other emotional issues. Socially, children who do not receive support often struggle to interact with peers or develop healthy social skills. Economically, the lack of support hinders access to quality education and healthcare, negatively affecting their overall quality of life. This article aims to identify the impacts of unmet child support rights and find effective ways to socialize these rights to the public. Using a literature analysis approach, the article proposes several strategies to raise public awareness about parental obligations to provide child support, including collaboration between the government, non-governmental organizations, and social media campaigns. Strengthening law enforcement is also crucial to ensure that negligent parents are held accountable according to the law. In conclusion, effective socialization and stricter law enforcement can help ensure the fulfillment of child support rights, which significantly impacts children’s welfare and development, leading to a better future for them.